The Place of Small Satellites In Fulfilling The Earth Observation Requirements of a Developing Country - (:unkn) unknown (IEEE, 2009)
Of the three or four major areas of use of satellites, Earth observation is probably the most attractive one for non-space-faring countries, in their aspirations to step into the space age. The expressed purpose to make use of space technologies for the benefit of the country covers both acquiring regional terrain data needed for development, and starting to build the infrastructure for further space efforts. Although building of remote sensing spacecraft may require a lower level of technology and a lower cost than communication or navigation satellites, the technical barriers and economic feasibility have still been too high for most developing countries to start a program of building observation satellites. Thus remote sensing still has been largely the realm of a few countries which have also dominated the commercial market for Earth imagery. All that may be changing though in, recent years with declining cost and size as well as more widely available electronic and sensor technologies. Ever smaller sizes, that is, micro, nano and pico satellites not only make it easier to build a satellite but also make it more affordable. The trend toward smaller satellites is also visible in well advanced space faring countries because the same mission objectives can be achieved more quickly and at a lower cost. This paper reviews the small satellite developments and lays out some proposals for fulfillment of the Earth observation reguirements of developing countries using small satellites. The proposals involve the capabilities and the numbers of small satellites, in regard to the requirements of resolution, revisit frequency, spectral bands and most importantly the economics. This paper should be especially meaningful for a country like Turkey which has a large area for natural resources monitoring and development, as well as a sensitive geopolitical position which makes it important to observe the region for security and defense.
Keywords: Remote sensing; small satellites; cost model; developing countries; constellations